Indoor Air Quality Level at Medical Clinics, University Hospital in Klang Valley, Malaysia - Ahmad, Subki; Abdull Hamid, Ermie; Ithnin, Anuar; Mohammad Pain, Izzatul Asyfah (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Patient health can be influenced by indoor air quality (IAQ) level, where the risks of IAQ pollution are proportionate with the occupant number in the clinic. This research aims to determine the level of IAQ in Medical Clinic 1 and 2 of University Hospital in Klang Valley, Malaysia. Methods: The indoor exposure to physical (temperature, relative humidity and air movement), chemical (formaldehyde, CO2 , CO, TVOC and PM10) and biological (bacterial and fungal count) parameters following Industry Code of Practice (ICOP) IAQ (2010) were assessed in the morning and afternoon using relevant equipment. Data was analysed with One-Sample T Test and Independent T Test using SPSS Version 25. Results: No statistically significant mean difference (p>0.05) of IAQ parameters between both Medical Clinics (morning & afternoon) except for Rh and CO by Independent T Test analysis. In contrast, the One-Sample T Test showed there was statistically significant mean difference (p<0.01) of all parameters as compared to the ICOP (2010) standard in both Medical Clinics (morning and afternoon). There was a positive correlation of CO2, CO and formaldehyde with bacterial counts (TBC) for both Medical Clinics. Meanwhile, CH2O concentration was slightly higher in the morning due to the usage of cleaning products which may have released CH2O gas killing the bacteria, thus lower the rate of bacterial growth in the afternoon. Fungal counts showed no significant impact. Conclusion: All measured parameters were complied with the ICOP (2010) standard except air movement and CO2 in both Medical Clinics.